ANALISIS ARUS, TEGANGAN, DAYA, ENERGI, DAN BIAYA PADA SENSOR PZEM-004T BERBASIS NODEMCU ESP8266 - Antara, Made Adi surya; Suteja, Wayan Arsa (Patria Artha Technological Journal, 2021)
Readings of the amount of current, voltage and electric power can be done using a sensor. One of the sensors for the amount of voltage, power and energy is in the form of the PZEM-004T model which is connected to the installed electrical load. The microcontroller used is the NodeMCU esp8266 microcontroller which functions as the main control system that will be connected to a computer, with the aim of being able to monitor it in real time in the future. By conducting experiments on the assembly of the PZEM-004T sensor module with NodeMCU esp8266 and making comparisons of the current measurements obtained from the PZEM-004T model sensor readings with the clamp meter current measuring instrument. The results of this study are a data measurement of current, voltage, power, energy, and the cost of household electrical energy consumption as well as the percentage error results from the comparison of current readings, on the PZEM-004T sensor with a reading from a clamp meter measuring instrument. By holding this research, researchers hope to obtain data on how much error percentage is obtained from the application of the PZEM-004T sensor, so that later from the results of the experiment, the PZEM-004T sensor is able to properly and properly monitor the use of electricity in household loads